Fresno County Women Lawyers' Installation of Officers Dinner Meeting - Watkins, Howard::::::::: (1988)
California Women Lawyers President Pauline Weaver swearing in 1988 Fresno County Women Lawyers Officers: Ruth Ratzlaff, Karen Burt, Karen Kern, and Hon. Sandra Snyder-Hylton